Penerapan media pembelajaran mading interaktif untuk meningkatkan hasil belajar mata pelajaran IPAS Bab Tumbuhan Sumber Kehidupan di Bumi pada siswa kelas IV di MIN 10 Blitar th Pelajaran 2022/2023 - Latifah, Anis (Maliki Interdisciplinary Journal, 2024)
Learning media is an information device that is generally used in working together between teachers and students in achieving ideal learning goals. Learning media is expected to improve learning outcomes and facilitate a smooth, effective, and efficient learning process. This study expects to improve student learning outcomes by involving intuitive Mading media in IPAS subjects and to see if there are any remarkable differences in student learning outcomes using interactive Mading media. Quantitative methods are used in this class action study. class IV Imam Bonjol MIN 10 students of Blitar become a research sample. The results showed that the use of Mading Interactive media can further develop student learning outcomes in science learning in class IV Imam Bonjol MIN 10 Blitar. This is evident in the fact that, out of 28 students, the average score on the question work has increased from 70.71 in cycle 1 to 86.21 in cycle 2.